2020
DOI: 10.30773/pi.2019.0240
|View full text |Cite
|
Sign up to set email alerts
|

Defining Treatment Response, Remission, Relapse, and Recovery in First-Episode Psychosis: A Survey among Korean Experts

Abstract: Objective For the proper treatment of first-episode psychosis, assessment of treatment response, remission, relapse, and recovery is important. Therefore, the present study aimed to develop operational definitions of clinical outcomes in first-episode psychosis.Methods A questionnaire was developed by a panel of experts and underwent three revisions. The final survey was presented to 150 psychiatrists who were members of the Korean Society for Schizophrenia Research. Respondents selected factors that they beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Because a systematic review reported a mean relapse rate of 77% and 90% by 1 and 2 years, respectively, following antipsychotic discontinuation ( Zipursky et al, 2014 ), using the criteria for full recovery rather than remission criteria would be more appropriate. In the survey, Korean psychiatrists favored the definition of remission as the complete absence of positive and negative symptoms or scores ≤2 on each item of the PANSS ( Lee et al, 2020 ). Asian psychiatrists considered “absence of any relapse following first episode” as the most important criterion for antipsychotic discontinuation ( Hui et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because a systematic review reported a mean relapse rate of 77% and 90% by 1 and 2 years, respectively, following antipsychotic discontinuation ( Zipursky et al, 2014 ), using the criteria for full recovery rather than remission criteria would be more appropriate. In the survey, Korean psychiatrists favored the definition of remission as the complete absence of positive and negative symptoms or scores ≤2 on each item of the PANSS ( Lee et al, 2020 ). Asian psychiatrists considered “absence of any relapse following first episode” as the most important criterion for antipsychotic discontinuation ( Hui et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants were followed up for 12 weeks (81.29±12.11 days) and subgrouped as schizophrenia responders (SRs) or nonresponders (NRs) based on whether they reached the criteria of a 50% reduction of the baseline score evaluated with the PANSS, ie, SRs consisted of FEPs with PANSS reduction ≥50%, and NRs a reduction <50%. 30 , 31 Reduction in total PANSS score was calculated: 32 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…Although there are various criteria on how remission is defined, it essentially means a period of the disorder when symptoms are mild and/or there is no "active" psychosis [53]. When symptoms start to reappear after this mild or symptom-free period, and the patient is experiencing a worsening in functioning, we are talking about relapse [54,55]. Nonetheless, as mentioned previously, a third of patients might not relapse rather achieve recovery [50], a state where the patient is able to function both socially and occupationally and has considerable symptomatic improvement [55,56].…”
Section: Remission and Relapse (Stage 2)mentioning
confidence: 99%
“…Nonetheless, in most cases, the negative and depressive / anxiety-like symptoms [25] are highly dominant in-between relapses, affecting the patient's quality of life enormously [57]. Throughout a relapse the positive and hostilityrelated symptoms might particularly increase [25,55].…”
Section: Remission and Relapse (Stage 2)mentioning
confidence: 99%